USE OF SPONGE, Callyspongia basilana EXTRACT AS ADDITIVE MATERIAL ON TIGER SHRIMP CULTURE - Rosmiati Rosmiati; Emma Suryati; Arifuddin Tompo (Indonesian Aquaculture Journal, 2010)
Blue shrimp disease is one of the main problems in tiger shrimp culture. It reduces shrimp quality which eventually will decrease its market price. Blue shrimp is caused by deficiency of nutrition and additive materials such as carotene and other nutrient which function as vitamin source for important metabolic processes and formation of color profile in shrimp and fish. The aims of this study were to study the application effect of carotenoid extract of sponge Callyspongia basilana, as an additive material on the ability of shrimp to get back to normal state after suffering blue shrimp disease and survival rate of shrimp and to find out the optimal concentration of sponge carotenoid extract to cure the diseased shrimp. This study was consisted of two steps namely; (1). Extraction of sponge carotenoid by maseration and fractionation using acetone and petroleum ether solvents and (2), the application of carotenoid extract on the diseased shrimp. The research was arranged in a complete randomized design with four experiments consisted of (A). Control (without carotenoid extract); (B),(C), and (D) carotetoid extract addition of 3 mg/L, 6 mg/L, and 9 mg/L respectively with three replication each. The test animal used were blue diseased tiger shrimp with the density of 15 ind./container having 7.5–9.5 cm in size and the average weight of 5.5–10.0 g. The study showed that Callyspongia basilana carotenoid extract was able to change blue diseased shrimp to be normal within six days at the concentration of 9 mg/L. The highest survival rate was found in the experiment D (93.3%). Meanwhile, the lowest was obtained by the control population (13.3%) and the other two treatments were 80.0%(C) and 73.3% (B). The average of water quality parameters such as temperature, dissolved oxygen, pH, salinity, nitrite, and ammonia were in the suitable range for the growth and survival rate of tiger shrimp.